MAKNA SLOGAN “WE'LL TAKE CARE OF YOU WHEREVER YOU ARE" PADA IKLAN SAMSUNG INDIA - Lina Lina; Ressy Damayanti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2021)
The development of the world of advertising today causes many new products and services to appear. This study aims to determine the meaning of the message conveyed in the advertisement based on the signs contained in it. This study uses a qualitative methodology with semiotic theory by Roland Barthes, based on the signifier and denotation, connotation, and myth aspects so that the advertisement can be dissected in detail and find meaning in the advertisement. The meaning of the Samsung India advertisement shows that the services offered by Samsung India are unusual because Samsung is able to deliver services directly to the customer's location even though they have to travel long distances with several obstacles. Another new finding can be seen that the company, namely Samsung India, is a credible company because it continues to highlight the Samsung logo in the advertisement. Based on the results of the study, the researcher provides academic and practical advice. Academic advice is to get more in-depth teaching about Roland Barthes' semiotics so that in future research, this research can be a reference. Practical advice, Samsung India should continue to develop creative, informative and communicative ideas or themes from campaigns for future advertisements.